ADMINISTRATION RESERVATION SYSTEM FOR HOTEL ROOMS IN "XYZ" USING VISUAL BASIC 6.0 - Ardiansyah Ardiansyah; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2005)
The development of increasingly sophisticated computer that is very helpful in data processing still using manual systems. This often raises issues related to the accuracy of the data which resulted in delays in the process of service at the  hotel. In this context, the authors are interested in creating a program design palikasi a computerized hotel reservation. In this paper discussed about the hotel front office services division "XYZ", Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD), Normalization, and display the Microsoft Visual Basic 6.0